Effect of AAC partner training using video on peers' interpretation of the behaviors of presymbolic middle-schoolers with multiple disabilities*. (2nd October 2018) - Holyfield, Christine; Light, Janice; Drager, Kathryn; McNaughton, David; Gormley, Jessica
Abstract: Children require consistent responses from partners to their presymbolic behaviors in order to increase the frequency and variety of these behaviors and eventually build symbolic language. This study served as an initial attempt to evaluate the effect of AAC training on typically-developing peers' interpretation of the behavior of three students with multiple disabilities whose communication was presymbolic and idiosyncratic in nature. The study used a pretest–posttest control group design with 12 peers in each condition (i.e., experimental and control). During the pretest, peers in both groups were inaccurate in their interpretations of the behaviors of the students with multiple disabilities. During the posttest, peers who completed the training interpreted the behaviors of the students with multiple disabilities with statistically significantly higher accuracy than participants who did not complete the training. The training may be an effective intervention approach to increase the accuracy and consistency with which communication partners interpret the idiosyncratic behaviors of children with multiple disabilities. Future research should evaluate the efficacy of using such training to increase communication partners' identification of and responsivity to idiosyncratic behaviors within the context of real-world interactions.